Recognition of Financial Instruments International Standards of Financial Reporting The Importance of Based Organization - Kadirjanovich, Mahmudov Saidjamol (American Journal of Economics and Business Management, 2025)
The financial market of development in many countries of the world is defined as priority direction of increase in competitiveness of national economy. Therefore the developing countries for improvement of national innovative system and activation of innovative processes in production increase volumes of the financial market for support to the potential innovative enterprises. This article studies and measures aspects of the financial market and an economic benefit of mechanism, that the state will just not allocate grants for innovative projects of startups, and will begin to finance them on the principles of funds of the financial capital market in the evidence of Uzbekistan. For analysis abstraction techniques have been used and at assessment of profitability of securities IRR indicator is used. Have received result that in Uzbekistan the operating fund the capital market will be financially and economic and the socioeconomic effect from purchase of securities will be higher what from the mechanism of gratuitous allocation of the state grants.